An economic history of Indonesia, 1800-2010 - Zanden, J. L. van.; Marks, Daan. (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Based on new datasets, this book presents an economic history of Indonesia. It analyses the causes of stagnation of growth during the colonial and independence period, making use of new theoretical insights from institutional economics and new growth theory. The book looks at the major themes of Indonesian history: colonial exploitation and the successes and limitations of the post 1900 welfare policies, the price of instability after 1945, and the economic miracle after 1967. The book not only discusses economic change and development - or the lack thereof - but also the institutional and socio-political structures that were behind these changes. It also presents a lot of new data on the changing welfare of the Indonesian population, on income distribution, and on the functioning of markets for rice, credit and labour. Concluding with a discussion on whether the poor profited from the economic changes, this book is a useful contribution to Southeast Asian Studies and International Economics.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Indonesia -- Economic conditions